Ethnography and the City : Readings on Doing Urban Fieldwork. - Ocejo, Richard E. (Metropolis and modern life., 2012)
The only collection of its kind on the market, this reader gathers the work of some of the most esteemed urban ethnographers in sociology and anthropology. Broken down into sections that cover key aspects of ethnographic research, Ethnography and the City will expose readers to important works in the field, while also guiding students to the study of method as they embark on their own work.